Second-line FOLFOX chemotherapy versus active symptom control for advanced biliary tract cancer (ABC-06): a phase 3, open-label, randomised, controlled trial. Issue 5 (May 2021) - Lamarca, Angela; Palmer, Daniel H; Wasan, Harpreet Singh; Ross, Paul J; Ma, Yuk Ting; Arora, Arvind; Falk, Stephen; Gillmore, Roopinder; Wadsley, Jonathan; Patel, Kinnari; Anthoney, Alan; Maraveyas, Anthony; et al.
Summary: Background: Advanced biliary tract cancer has a poor prognosis. Cisplatin and gemcitabine is the standard first-line chemotherapy regimen, but no robust evidence is available for second-line chemotherapy. The aim of this study was to determine the benefit derived from second-line FOLFOX (folinic acid, fluorouracil, and oxaliplatin) chemotherapy in advanced biliary tract cancer. Methods: The ABC-06 clinical trial was a phase 3, open-label, randomised trial done in 20 sites with expertise in managing biliary tract cancer across the UK. Adult patients (aged ≥18 years) who had histologically or cytologically verified locally advanced or metastatic biliary tract cancer (including cholangiocarcinoma and gallbladder or ampullary carcinoma) with documented radiological disease progression to first-line cisplatin and gemcitabine chemotherapy and an Eastern Cooperative Oncology Group performance status of 0–1 were randomly assigned (1:1) centrally to active symptom control (ASC) and FOLFOX or ASC alone. FOLFOX chemotherapy was administered intravenously every 2 weeks for a maximum of 12 cycles (oxaliplatin 85 mg/m 2, L-folinic acid 175 mg [or folinic acid 350 mg], fluorouracil 400 mg/m 2 [bolus], and fluorouracil 2400 mg/m 2 as a 46-h continuous intravenous infusion). Randomisation was done following a minimisation algorithm using platinum sensitivity, serum albumin concentration, and stage as stratification factors. The primary endpoint was overall survival, assessed in the intention-to-treat population. Safety was also assessed in the intention-to-treat population. The study is complete and the final results are reported. This trial is registered with ClinicalTrials.gov, NCT01926236, and EudraCT, 2013-001812-30. Findings: Between March 27, 2014, and Jan 4, 2018, 162 patients were enrolled and randomly assigned to ASC plus FOLFOX (n=81) or ASC alone (n=81). Median follow-up was 21·7 months (IQR 17·2–30·8). Overall survival was significantly longer in the ASC plus FOLFOX group than in the ASC alone group, with a median overall survival of 6·2 months (95% CI 5·4–7·6) in the ASC plus FOLFOX group versus 5·3 months (4·1–5·8) in the ASC alone group (adjusted hazard ratio 0·69 [95% CI 0·50–0·97]; p=0·031). The overall survival rate in the ASC alone group was 35·5% (95% CI 25·2–46·0) at 6 months and 11·4% (5·6–19·5) at 12 months, compared with 50·6% (39·3–60·9) at 6 months and 25·9% (17·0–35·8) at 12 months in the ASC plus FOLFOX group. Grade 3–5 adverse events were reported in 42 (52%) of 81 patients in the ASC alone group and 56 (69%) of 81 patients in the ASC plus FOLFOX group, including three chemotherapy-related deaths (one each due to infection, acute kidney injury, and febrile neutropenia). The most frequently reported grade 3–5 FOLFOX-related adverse events were neutropenia (ten [12%] patients), fatigue or lethargy (nine [11%] patients), and infection (eight [10%] patients). Interpretation: The addition of FOLFOX to ASC improved median overall survival in patients with advanced biliary tract cancer after progression on cisplatin and gemcitabine, with a clinically meaningful increase in 6-month and 12-month overall survival rates. To our knowledge, this trial is the first prospective, randomised study providing reliable, high-quality evidence to allow an informed discussion with patients of the potential benefits and risks from second-line FOLFOX chemotherapy in advanced biliary tract cancer. Based on these findings, FOLFOX should become standard-of-care chemotherapy in second-line treatment for advanced biliary tract cancer and the reference regimen for further clinical trials. Funding: Cancer Research UK, StandUpToCancer, AMMF (The UK Cholangiocarcinoma Charity), and The Christie Charity, with additional funding from The Cholangiocarcinoma Foundation and the Conquer Cancer Foundation Young Investigator Award for translational research.